A polyphenol-loaded silicon oxide hydrogel test paper and its preparation method and application

Through the polyphenol-loaded silica hydrogel test strip, combined with resveratrol and silica hydrogel, the problem of slow detection speed and poor accuracy of ammonia water or ammonia gas concentration in the prior art is solved, and a fast, accurate and portable detection effect is achieved.

CN115308198BActive Publication Date: 2025-02-28TONGJI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211030710.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-26
Publication Date
2025-02-28
Estimated Expiration
2042-08-26

AI Technical Summary

Technical Problem

The prior art is difficult to quickly and accurately detect the concentration of ammonia water or ammonia, and commonly used testing instruments are long, costly, and are not portable.

Method used

Using a silicon oxide hydrogel test strip for loading polyphenols, the reaction is accelerated by combining resveratrol with silica hydrogel, and the porous structure of silica hydrogel is used to accelerate the reaction, achieving rapid detection.

Benefits of technology

It realizes the detection of ammonia water and ammonia concentrations with simple operation, high sensitivity and fast response speed. It is suitable as a fast detection method for ammonia, with low cost and easy to carry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115308198B_ABST
    Figure CN115308198B_ABST
Patent Text Reader

Abstract

The present invention relates to a kind of ammonia detection test paper, in particular to a kind of polyphenols loaded silicon oxide hydrogel test paper and its preparation method and application, including the following steps: S1: tetraethyl orthosilicate, ethanol, deionized water and hydrofluoric acid are mixed to obtain a precursor solution of silicon oxide hydrogel; S2: polyphenols are added to the precursor solution of silicon oxide hydrogel, stirred and ultrasonically dispersed to completely dissolve, and then hydrofluoric acid is added dropwise thereto to adjust the viscosity of the mixed solution; S3: the test paper template is completely inserted into the mixed solution, and then the test paper template is pulled for coating to obtain a test paper with silicon oxide polyphenols hydrogel; S4: the test paper with silicon oxide polyphenols hydrogel is aged and dried to obtain a polyphenols loaded silicon oxide hydrogel test paper. Compared with the prior art, the preparation method of the present invention is simple, raw materials are easy to obtain, cost is low, the prepared test paper is easy to carry, concentration detection is fast and accurate, and it is suitable for practical use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an ammonia detection test paper, and in particular to a polyphenol-loaded silicon oxide hydrogel test paper and a preparation method and application thereof. Background Art

[0002] Liquid ammonia / ammonia gas is an important industrial raw material and refrigerant, and is widely used in industrial production. Ammonia is colorless and has a pungent odor. It is toxic and corrosive. According to relevant statistics, ammonia is one of the hazardous chemicals with the highest accident rate in industrial production. In view of the unique physical and chemical properties of ammonia, the potential leakage risk during use cannot be underestimated. High concentrations of ammonia are fatal to the human body. According to national safety standards, the maximum allowable concentration of ammonia per cubic meter of air is 30 mg. Therefore, the determination of environmental ammonia concentration often requires proprietary testing instruments, but such testing instruments often have long testing times, high costs, and are difficult to carry and use; while the low-cost and easy-to-carry test strips are limited by the reaction speed and cannot quickly and accurately obtain the concentration of ammonia water or ammonia gas. Therefore, in industrial production, a test strip that does not rely on instruments and can quickly detect concentrations is urgently needed.

[0003] Plant extract resveratrol is a non-flavonoid polyphenol compound. It is an antitoxin produced by many plants when stimulated. It can be synthesized in grape leaves and grape skins and is a biologically active ingredient in wine and grape juice. Resveratrol changes color when it encounters ammonia gas or ammonia solution. As a natural active ingredient, resveratrol is commonly found in more than 70 plants in nature and has a wide range of extraction sources. It has almost no toxic side effects, low safety risks, and is widely used.

[0004] However, resveratrol itself is difficult to directly apply to ammonia test strips because it is insoluble in water, has poor stability, and is easily decomposed. Summary of the invention

[0005] The purpose of the present invention is to solve at least one of the above problems and to provide a polyphenol-loaded silica hydrogel test paper and a preparation method and application thereof. The test paper is easy to operate, has good sensitivity and fast response speed.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] The first aspect of the present invention discloses a method for preparing a polyphenol-loaded silica hydrogel test paper, comprising the following steps:

[0008] S1: Tetraethyl orthosilicate, ethanol, deionized water and hydrofluoric acid are mixed to obtain a precursor solution of silica hydrogel;

[0009] S2: adding polyphenols to the precursor solution of the silica hydrogel obtained in step S1, stirring and ultrasonically dispersing until completely dissolved, and then dropping hydrofluoric acid therein to adjust the viscosity of the mixed solution;

[0010] S3: inserting the test paper template completely into the mixed solution obtained in step S2, and then pulling up the test paper template for coating to obtain a test paper with silicon oxide-polyphenol hydrogel attached;

[0011] S4: aging and drying the test paper with the silicon oxide-polyphenol hydrogel obtained in step S3 to obtain the polyphenol-loaded silicon oxide hydrogel test paper.

[0012] Preferably, in step S1, the volume ratio of tetraethyl orthosilicate, ethanol, deionized water and hydrofluoric acid is 16:8:2:0.01.

[0013] Preferably, in step S2, the polyphenolic substance is resveratrol, and the added amount is 10-20 mg resveratrol / mL ethanol.

[0014] Preferably, in step S2, the stirring speed is 400-600 r / min.

[0015] Preferably, in step S2, the ultrasonic dispersion is performed at 20°C for 30 minutes to allow the polyphenols to be fully dissolved and mixed in the silica hydrogel.

[0016] Preferably, in step S2, the viscosity of the mixed solution is adjusted to 4000-6500 mPa·s.

[0017] Preferably, in step S3, the thickness of the film after the test paper template is pulled and coated does not exceed 2 mm. The film is coated by pulling so that the silicon oxide-polyphenol hydrogel is attached to the surface of the test paper, which is easy to operate, suitable for automated operation, and can also be manually operated, which can meet a variety of situations. Controlling the film thickness to be no more than 2 mm can effectively avoid the thickness difference of the prepared test paper and affect the detection performance, thereby improving the detection consistency of the test paper.

[0018] Preferably, the aging in step S4 is to place the test paper with the silicon oxide-polyphenol hydrogel in an ethanol solution containing resveratrol and age it at room temperature for 1-2 days.

[0019] Preferably, the drying in step S4 is performed in an oven at 50° C. for 1 day.

[0020] The second aspect of the present invention discloses a polyphenol-loaded silicon oxide hydrogel test paper, which is prepared by any of the above-mentioned preparation methods.

[0021] The third aspect of the present invention discloses an application of the polyphenol-loaded silica hydrogel test paper in the detection of ammonia water and ammonia gas concentrations.

[0022] Resveratrol itself is insoluble in water, but soluble in some organic solvents. The present invention uses this property to make it fully soluble in a silica hydrogel precursor solution to prepare a silica hydrogel test paper loaded with polyphenols that can be used to detect ammonia gas and ammonia water. Further, the present invention utilizes silica hydrogel, which belongs to porous nanomaterial silica hydrogel, which has the advantages of high porosity and high adsorption. Silica hydrogel loaded with resveratrol can not only overcome the original special physical and chemical properties of being insoluble in water and easy to decompose, but also improve stability and utilization. The porous structure of silica hydrogel can also increase the reaction rate and the rate of color change reaction, thereby effectively distinguishing the concentration of ammonia water and ammonia gas.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The preparation method of the present invention is simple, the raw materials are easy to obtain, the cost is low, and the prepared test paper is easy to carry, can quickly and accurately detect the concentration of ammonia water and ammonia gas, and is suitable for use as a rapid detection method for ammonia.

[0025] 2. The test paper prepared by the method of the present invention has the advantages of miniaturization, portability and precision, and has low requirements for the detection environment such as temperature, humidity, and light. The concentration of ammonia water can be preliminarily reflected from the color depth of the test paper, and a relatively accurate ammonia concentration can be obtained by the reflectivity of the test paper, and it has excellent selectivity in detection.

[0026] 3. The resveratrol in the present invention is loaded on the silica hydrogel, which effectively overcomes its own problems of being difficult to dissolve and easy to decompose, improves its stability and utilization, and provides a faster reaction rate for resveratrol through the high porosity of the silica hydrogel, so that the test paper can have a rapid measurement effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a schematic diagram of the structure of the polyphenol-loaded silicon oxide hydrogel test paper prepared in Example 1 of the present invention;

[0028] Figure 2 This is a schematic diagram of the test results of the polyphenol-loaded silicon oxide hydrogel test paper prepared in Example 1 of the present invention;

[0029] Figure 3 The graph of the diffuse reflectance change of silicon oxide hydrogel test paper loaded with polyphenols of different concentrations after adding ammonia water of the same concentration;

[0030] Figure 4 This is a comparison diagram of infrared spectra of the silicon oxide-resveratrol gel (RSA) prepared in Example 1 of the present invention, pure silicon oxide (SA) and resveratrol powder (Res);

[0031] Figure 5 SEM images of pure silicon oxide (A), resveratrol powder (B) and silicon oxide-resveratrol nano drug delivery system (C);

[0032] Figure 6 TEM images of pure silica (A), resveratrol powder (B) and silica-resveratrol nanodrug delivery system (C, D). DETAILED DESCRIPTION

[0033] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but do not limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some variations and improvements can also be made without departing from the inventive concept. In the following examples, each raw material is commercially available raw material.

[0034] Example 1

[0035] 1) Tetraethyl orthosilicate solution, ethanol, deionized water and hydrofluoric acid are respectively mixed uniformly in a volume ratio of 16:8:2:0.01 to prepare a precursor solution of silicon oxide hydrogel.

[0036] 2) Add resveratrol powder to the precursor solution of silica hydrogel at a dosage of 10-20 mg of resveratrol powder per 1 mL of ethanol.

[0037] 3) At room temperature, the precursor solution of the silica hydrogel to which the resveratrol powder was added was stirred at a rate of 500 r / min (stirring rate of the aqueous phase).

[0038] 4) Performing ultrasonic dispersion for 30 minutes at a water temperature of 20° C. to completely dissolve resveratrol in the precursor solution of the silica hydrogel to obtain a mixed solution.

[0039] 5) Hydrofluoric acid is added dropwise to the mixed solution to adjust and control the viscosity of the mixed solution within the range of 4000-6500 mPa·s, and then ordinary polymer absorbent paper is completely inserted into the mixed solution as a template of the gel test paper.

[0040] 6) After waiting for a period of time, the absorbent paper is slowly pulled upward at a constant speed for coating, so that the viscous hydrogel precursor is attached to the absorbent paper. The coating thickness needs to be controlled within 2 mm. After the pulling is completed, the test paper is allowed to stand at room temperature for 5 minutes to obtain a test paper with resveratrol-silicon oxide hydrogel attached.

[0041] 7) The test paper was placed in an ethanol solution containing resveratrol and aged for 2 days.

[0042] 8) The aged test paper was placed in an oven at 50° C. for 1 day for drying to obtain a resveratrol-silicon oxide hydrogel test paper.

[0043] like Figure 1 As shown, the absorbent paper is loaded with resveratrol-silicon oxide hydrogel, which has a network structure and a large number of channels, so that the contact between resveratrol and ammonia can be more complete, thereby accelerating the reaction.

[0044] like Figure 2 As shown, after adding ammonia water of different concentrations to the test paper, after the same period of time, the color of the test paper has obvious changes and there is a certain difference between them, which can be used as a standard for identifying concentration.

[0045] like Figure 3 As shown in the figure, 1 mL of ammonia water of the same concentration was added to the hydrogel test papers of different concentrations, and then the test papers were tested for diffuse reflectance. It can be seen that the hydrogel test papers with higher concentrations have a higher reflectance of 500-1000 cm -1 The wavelengths in this range show higher reflectivity. Table 1 shows the changes in reflectivity of hydrogel test papers with different concentrations as the concentration of ammonia increases. Figure 3 As shown in Table 1, the diffuse reflectance at a fixed wavelength increases with the increase of resveratrol concentration. When the concentration of the added ammonia water changes, the diffuse reflectance of the gel test paper also changes, increasing with the increase of the concentration of the added ammonia water. After testing, within a certain range, the ammonia water concentration and the reflectance of the test paper have a good linear relationship, and have excellent selectivity in detection.

[0046] Table 1 Changes in diffuse reflectance of hydrogel test paper after adding ammonia water (1 mL)

[0047]

[0048] like Figure 4 The following are the FTIR spectra of resveratrol, silicon oxide and silicon oxide-resveratrol hydrogel. The infrared spectrum of resveratrol shows the following main peaks. -1 The peaks near 1600 cm are assigned to free OH stretching vibrations; -1 and 1583cm -1 The double peak at 1504 cm -1 and 1443cm -1 The peak at 1378 cm reflects the benzene skeleton vibration and CC stretching vibration. -1This is evidenced by the peak at 1063cm -1 and 963cm -1 The peak at 1200-1000 cm is attributed to the bending vibration of C=CH, which indicates that resveratrol has changed. -1 A peak appears at , which is the Si-O tetrahedral symmetric vibration peak of the strong covalent bond vibration of silicon and oxygen atoms. This wave number region reveals the existence of a silicon network (Si-O-Si).

[0049] Figure 5 The results of scanning electron microscopy (SEM) show that the sample has a typical nanoporous structure, and the skeleton particles are loose and evenly distributed. Pure silicon oxide (Figure A) has a tightly interconnected nanostructure network; resveratrol (Figure B) presents a flaky structure and obvious geometric edges, which is a normal phenomenon of freeze-dried powder. In the silicon oxide-resveratrol gel (RSA) (Figure C) prepared in this example, resveratrol is wrapped by silicon oxide, which can improve its stability.

[0050] Figure 6 The results of transmission electron microscopy (TEM) are shown in Figure 1. Pure silicon oxide (Figure A) has a small particle size under transmission electron microscopy and a certain network skeleton structure. The particle size of silicon oxide-resveratrol gel (RSA) (Figures C and D show the scanning results of TEM at different positions at 200nm) is significantly larger than that of pure silicon oxide. The center is high-density and low-permeability, which is the form of silicon oxide wrapped around resveratrol.

[0051] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a polyphenol-loaded silica hydrogel test paper, characterized in that: The steps include: S1: Tetraethyl orthosilicate, ethanol, deionized water and hydrofluoric acid are mixed to obtain a precursor solution of silica hydrogel; S2: adding polyphenols to the precursor solution of the silica hydrogel obtained in step S1, stirring and ultrasonically dispersing until completely dissolved, and then dropping hydrofluoric acid therein to adjust the viscosity of the mixed solution; S3: inserting the test paper template completely into the mixed solution obtained in step S2, and then pulling up the test paper template for coating to obtain a test paper with silicon oxide-polyphenol hydrogel attached; S4: aging and drying the test paper with the silicon oxide-polyphenol hydrogel obtained in step S3 to obtain the polyphenol-loaded silicon oxide hydrogel test paper; In step S2, the polyphenolic substance is resveratrol, and the added amount is 10-20 mg resveratrol / mL ethanol.

2. The method for preparing a polyphenol-loaded silicon oxide hydrogel test paper according to claim 1, wherein: In step S1, the volume ratio of tetraethyl orthosilicate, ethanol, deionized water and hydrofluoric acid is 16:8:2:0.

01.

3. The method for preparing a polyphenol-loaded silicon oxide hydrogel test paper according to claim 1, characterized in that: In step S2, the ultrasonic dispersion is performed at 20° C. for 30 min.

4. The method for preparing a polyphenol-loaded silicon oxide hydrogel test paper according to claim 1, characterized in that: In step S2, the viscosity of the mixed solution is adjusted to 4000-6500 mPa·s.

5. The method for preparing a polyphenol-loaded silicon oxide hydrogel test paper according to claim 1, characterized in that: In step S3, the thickness of the film after the test paper template is coated does not exceed 2 mm.

6. The method for preparing a polyphenol-loaded silicon oxide hydrogel test paper according to claim 1, characterized in that: In step S4, the aging is as follows: placing the test paper with the silicon oxide-polyphenol hydrogel in an ethanol solution containing resveratrol, and aging at room temperature for 1-2 days.

7. The method for preparing a polyphenol-loaded silicon oxide hydrogel test paper according to claim 1, characterized in that: In step S4, the drying is performed in an oven at 50° C. for 1 day.

8. A polyphenol-loaded silica hydrogel test paper, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the polyphenol-loaded silicon oxide hydrogel test paper as claimed in claim 8 in the detection of ammonia water and ammonia gas concentrations.

Citation Information

Patent Citations

  • Curcumin-silicon oxide nano drug-loading system as well as preparation method and application thereof

    CN114209851A

  • Fluorescent compound for detection of isocyanate substances, preparation method therefor and use thereof as test-paper-type detection probe

    WO2021000467A1